Beginning of the State Security Operations against Exarch Stefan during the 40s of the 20th Century - Nikolchev, Dilyan (Forum Theologicum Sardicense, 2025)
Dilyan Nikoltshev, Beginning of the State Security Operations against Exarch Stefan during the 40s of the 20th Century. The life of the third Bulgarian Exarch, Stefan, has been the subject of numerous studies. As the leader of the Orthodox Church, which was the main ideological opponent of the Communist state, Exarch Stefan was the target of many attempts at discreditation by the Communist Security Service of Bulgaria. He likely became a person of interest for state security from the very early days of the Communist regime in Bulgaria. This study aims to determine when the Security Service began its campaign against Exarch Stefan, based on extensive materials from the archives of the Ministry of Internal Affairs and other institutions in Bulgaria.